Volume 6B: Energy 2013
DOI: 10.1115/imece2013-64884
|View full text |Cite
|
Sign up to set email alerts
|

Flash Boiling and Desorption From a Macroporous Carbon-Boron-Nitrogen Foam

Abstract: This paper presents a tunable cooling technology befitting fast transient thermal events. In this approach, the rapid depressurization of the working fluid triggers coincident flash-boiling and desorption events, thereby achieving very high cooling rates for short periods of time. Carbon-boron-nitrogen foam, derived through the chemical modification of a highly graphitized carbon precursor, is utilized because of its excellent thermal conductivity, adsorptive properties and open macroporous structure. Prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The homogeneous transesterification reaction could operate at atmospheric pressure. However, we operate the CSTR at 1.5 bar absolute pressure, by supplying nitrogen gas, to guarantee that methanol remains in the liquid phase at the nominal operating temperature as the bubble point of methanol at 1 bar is 65 °C . We adopt the operating conditions that are optimal according to Zhang et al (2003) and Abbaszaadeh et al.…”
Section: Process Description and Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homogeneous transesterification reaction could operate at atmospheric pressure. However, we operate the CSTR at 1.5 bar absolute pressure, by supplying nitrogen gas, to guarantee that methanol remains in the liquid phase at the nominal operating temperature as the bubble point of methanol at 1 bar is 65 °C . We adopt the operating conditions that are optimal according to Zhang et al (2003) and Abbaszaadeh et al.…”
Section: Process Description and Operating Conditionsmentioning
confidence: 99%
“…However, we operate the CSTR at 1.5 bar absolute pressure, by supplying nitrogen gas, to guarantee that methanol remains in the liquid phase at the nominal operating temperature as the bubble point of methanol at 1 bar is 65 °C. 66 We adopt the operating conditions that are optimal according to Zhang et al (2003) 10 and Abbaszaadeh et al (2012) 13 to achieve maximum conversion. We thus operate the CSTR at the optimal residence time of the reactor content of 1 h. The amount of total methanol fed into the reactor is determined such that an optimal 6:1 methanol-to-oil mole ratio entering the reactor is achieved.…”
Section: Industrial and Engineeringmentioning
confidence: 99%
“…Once nucleation is initiated (either by heterogeneous or homogeneous nucleation), the liquid begins to undergo rapid phase-change [121][122][123][124][125][126]. The phenomenon of flash boiling has been studied for understanding boiling liquid exploding vapor expansion (BLEVE) accidents associated with pressurized vessels that rupture [123,124], for improving fuel atomization to enhance combustion efficiencies in engines [127], and more recently, for rapid cooling of electronic devices involving power pulsations [46,[128][129][130].…”
Section: Combined Phase Change Material-heat Pipe/vapormentioning
confidence: 99%
“…In their experimental work, it was shown that the transient flash cooling process takes place rapidly within a time span of 1 s. The cooling device was able to maintain temperatures within 6 5 C, even at a high heat flux of 104 W/ cm 2 . In earlier work, Engerer et al [128] studied flash boiling of methanol in chambers with and without porous foam structures. These high thermal conductivity structures were provided to increase the convective heat transfer area and bubble nucleation sites.…”
Section: Combined Phase Change Material-heat Pipe/vapormentioning
confidence: 99%